2013
DOI: 10.1371/journal.pone.0063788
|View full text |Cite
|
Sign up to set email alerts
|

Direct Medical Cost of Influenza-Related Hospitalizations among Severe Acute Respiratory Infections Cases in Three Provinces in China

Abstract: BackgroundInfluenza-related hospitalizations impose a considerable economic and social burden. This study aimed to better understand the economic burden of influenza-related hospitalizations among patients in China in different age and risk categories.MethodsLaboratory-confirmed influenza-related hospitalizations between December 2009 and June 2011 from three hospitals participating in the Chinese Severe Acute Respiratory Infections (SARI) sentinel surveillance system were included in this study. Hospital bill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
39
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(49 citation statements)
references
References 11 publications
6
39
4
Order By: Relevance
“…Our study of the direct medical costs of laboratory-confirmed influenza hospitalizations in patients aged 65 y in Spain found the mean cost per case was € 3,219, higher than the € 2,490 found in Poland, 14 the € 1,570.3 found in China, 27 or the € 1,270€ (in terms of 2011 purchasing power) reported in Italy. 28 The reduction in cost of 2.5% in vaccinated cases in our study came mainly from the reduction in the ICU stay, sparing mechanical ventilation and preventing secondary bacterial pneumonia.…”
Section: Discussioncontrasting
confidence: 52%
“…Our study of the direct medical costs of laboratory-confirmed influenza hospitalizations in patients aged 65 y in Spain found the mean cost per case was € 3,219, higher than the € 2,490 found in Poland, 14 the € 1,570.3 found in China, 27 or the € 1,270€ (in terms of 2011 purchasing power) reported in Italy. 28 The reduction in cost of 2.5% in vaccinated cases in our study came mainly from the reduction in the ICU stay, sparing mechanical ventilation and preventing secondary bacterial pneumonia.…”
Section: Discussioncontrasting
confidence: 52%
“…The median cost of the P&I hospitalizations during the study period was 2625 RMB (equal to 423 USD with a ratio of 1 USD:6.2 RMB); this cost was a little lower than that found in our previous study conducted with children hospitalized with influenza infection (624 USD), but much higher than the result of another study from China of 231 USD per influenza hospitalization among children ≤15 years from 2009 to 2011 . These differences are influenced by local economics, as the income and salary are higher in Suzhou than in other areas of China, and the definition of the diseases varies between the studies.…”
Section: Discussionmentioning
confidence: 57%
“…2). The potential for the interventions to be cost-saving was only estimated when we assumed a severe illness treatment cost for each CRI case (US $525, 3255 RMB) [22]. This is an extreme scenario and is unlikely except in a highly pathogenic influenza epidemic/pandemic where a mean case requires substantial healthcare treatment.…”
Section: Sensitivity Analysis Resultsmentioning
confidence: 99%
“…The exclusion of these factors will make our results more conservative. HCWs are known to transmit various types of nosocomial infections to patients [34] and the literature indicates that there are likely to be substantial benefits if the number of patients with CRI is reduced [22]. For example, the benefits of preventing HCW infection transmission through vaccination have been observed in long-term care facilities that found an associated decrease in mortality in their elderly residents [35][36][37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation